Translation Narration, Media and the Staging of Differences - Rößner, Michael 1973-; Italiano, Federico 1976- (transcript Verlag, 2012)
As recent years have revealed, the concept of »translation« has grown increasingly important in a globalizing world and a multi-media society. Seeing translation as the negotiation of differences in identity construction does not only contribute to the understanding of contemporary cultural processes - it also makes it possible to find orientation and critical insights in a world of constantly changing social, political and media spaces.This collection of essays discusses the »translational turn«, proposing new theoretical approaches and providing new insights into the relation between narration and identity construction, between translation processes and the media
Keywords: Culture; Media; Theatre; Language; Cultural Theory; Cultural studies; Postcolonialism; Literature; Identity; General Literature Studies; Narration; Transnationalisierung; Interkulturalität; Medien; Kulturübertragung; Globalisierung; Darstellung; Das Andere; Kulturelle Identität; Konferenzschrift -- 2010 -- Wien